(untitled) (The Research of Medical Science Review, 2025)
Pancreatic cancer remains one of the deadliest malignancies globally, with late diagnosis and aggressive progression contributing to its poor prognosis. Recent studies continue to strengthen the evidence that metabolic disorders, specifically diabetes and obesity, significantly influence both the risk and outcomes of pancreatic cancer.